Pembenahan Terhadap Siklus Keuangan Menggunakan Metode Value For Money Pada Badan Keuangan Dan Aset Daerah Kota Medan - Imsar Imsar; Rizky Febrian Saragih (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The goals of this study are to: (1) analyze the day-to-day operations of the Bank for Foreign Exchange in Kota Medan; and (2) determine if the procedures for opening bank accounts there comply with the rules governing pending transactions. (1) Value for money-focused banking work at BPK Kota Medan is very good and adheres to three principles: efficacy, effectiveness, and warning; and (2) Opening a bank account at the BPK Kota Medan. This means that business initiatives must be carried out in a way that maximizes financial resources and is especially focused on the needs of the general populace or the local populace.